The night travelers [large type] - Correa, Armando Lucas, 1959- (Center Point Large Print, 2023)
"Berlin, 1931: Ally Keller, a talented young poet, is alone and scared when she gives birth to a mixed-race daughter she names Lilith. As the Nazis rise to power, Ally knows she must keep her baby in the shadows to protect her against Hitler's deadly ideology of Aryan purity. But as she grows, it becomes more and more difficult to keep Lilith hidden, so Ally sets in motion a dangerous and desperate plan to send her daughter across the ocean to safety. Havana, 1958: Now an adult, Lilith has few memories of her mother or her childhood in Germany. Besides, she's too excited for her future with her beloved Martín, a Cuban pilot with strong ties to the Batista government. But as the flames of revolution ignite, Lilith and her newborn daughter, Nadine, find themselves at a terrifying crossroads. Berlin, 1988: As a scientist in Berlin, Nadine is dedicated to ensuring the dignity of the remains of all those who were murdered by the Nazis. Yet she has spent her entire lifetime avoiding the truth about her own family's history. It takes her daughter, Luna, to encourage Nadine to uncover the truth about the choices her mother and grandmother made to ensure the survival of their children. And it will fall to Luna to come to terms with a shocking betrayal that changes everything she thought she knew about her family's past."--